Childhood respiratory allergies and symptoms in highly polluted area of Central Europe. Issue 1 (2nd January 2019) - Puklová, Vladimíra; Žejglicová, Kristýna; Kratěnová, Jana; Brabec, Marek; Malý, Marek
ABSTRACT: The study investigated the associations between the prevalence of the childhood respiratory diseases and the long-term exposure to air pollution in the burdened area of Moravian–Silesian Region in the Czech Republic. The health data were collected during 2014 in 7, 239 children 5, 9, 13 and 17 years of age. Exposure to PM10 and NO2 in the residence addresses was based on dispersion models and GIS based traffic-related indicators. PM10 levels were positively associated with both lifetime (OR 1.35; 95%CI 1.09–1.67) and current (OR 1.32; 95%CI 1.05–1.67) allergic rhinitis; current asthma was associated negatively. The associations between traffic indicator and respiratory health were not found. On the other hand, marked positive associations were found between the respiratory diseases and symptom severity structured into ordinal variables, and PM10 and NO2 . Modelled long-term exposure to air pollution was associated with childhood allergic rhinitis and deterioration of the respiratory symptoms.